Konten Iklan Media Sosial PT Adnyana International Development Dalam Meningkatkan Engagement - Hammamiardi, Helmi Aji; Soraya, Iin; Ekowati, Sari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
PT Adnyana International Development, which is one of the property developers in Bali, is trying to reach customers and audiences by engaging in activities on social media. In that effort they also advertise on social media so that they can reach a wider audience. In addition to creating attractive advertisement content can increase engagement on their social media from the results of the advertisements run. The objective of this research is to understand and describe the content of PT Adnyana International Development's social media advertisements in enhancing engagement. This research uses a qualitative descriptive research method. This research aims to determine the results of the social media advertising content of PT Adnyana International Development that can enhance engagement.